Survival outcomes in IIIC cervical cancer by treatment strategies: a systematic review and meta-analysis - Yi-xiang Li; Si-yu Cao; Yu Fan; Yu-fei Zhang; Jin-ke Li (BMC Cancer)
Abstract Objective To compare survival outcomes of patients with stage IIIC cervical cancer based on different treatment strategies. Method Studies reporting survival of cervical cancer patients in IIIC stage were identified through systematic searches of the PubMed, Web of Science, CNKI and Wanfang data, and the hazard ratios (HRs) of survival outcomes were calculated based on different treatment strategies: radical hysterectomy (RH) group versus radical chemoradiotherapy (RCRT) group. Heterogeneity in the pooled data was assessed using the I² statistic. Results We meta-analyzed data from nine studies involving 6,793 patients, who were assigned to different treatment strategies: RH group, 3840 patients (56.5%) and RCRT group, 2,953 patients (43.5%). High heterogeneity was observed across studies. Compared to the RCRT group, the RH group showed similar overall survival (HR 0.77, 95% CI 0.58–1.04, I² =83.4%), disease-free survival (HR 0.68, 95% CI 0.23–2.04, I² =88.3%) and progression-free survival (HR 0.67, 95% CI 0.10–4.36, I² =91.4%). Conclusions Current evidence suggests no statistically significant survival difference between RCRT and RH in IIIC cervical cancer. These findings don’t contradict the NCCN recommendation, but the high heterogeneity and wide confidence intervals warrant cautious interpretation due to potential variations in patient populations or treatment protocols.